The extent to which Libyan commercial banks granting banking Murabaha are committed to Sharia Standard No. (8) regulating Murabaha transactions issued by the AAOIFI Authority. (Economic studies journal, 2023)
Abstract This study dealt with the Islamic banking financing (Murabaha) which is applied in Libyan commercial banks, and the suspicions raised about its practical reality related to its inconsistency with the controls and provisions of Islamic law. Therefore, the study aimed to identify the extent to which Libyan commercial banks adhere to Sharia Standard No. (8) regulating Murabaha operations issued by the Accounting and Auditing Organization for Islamic Financial Institutions known as “AAOIFI” when granting banking Murabaha. The study relied on the descriptive research method, whereby the deductive thinking method used in descriptive research was followed, which supports and establishes the theoretical reference for the hypotheses of the study. Explanations of the problem of the study The study concluded that the Libyan banks studied did not comply with all the requirements and controls of the Sharia Murabaha Standard No. (8) issued by the (AAOIFI).